Fibrin monomers evaluation during hospitalization for COVID-19 is a predictive marker of in-hospital mortality - Smadja, David M.; Gendron, Nicolas; Philippe, Aurélien; Diehl, Jean-Luc; Ochat, Nadège; Bory, Olivier; Beauvais, Agathe; Mareau, Alexis; Jannot, Anne-Sophie; Chocron, Richard (Frontiers in Cardiovascular Medicine, 2023)
Background: Coagulopathy is one of the main triggers of severity and worsening in Coronavirus disease 2019 (COVID-19) particularly in critically ill patients. D-dimer has been widely used to detect COVID-19 coagulation disorders and has been correlated with outcomes such as disease severity and in-hospital mortality. Involvement of other fibrin degradation products, particularly fibrin monomer (FM) remains an ongoing question. Methods: We performed a monocentric study of adult patients with COVID-19, who were hospitalized in medical ward (MW) or in intensive care unit (ICU) who had FM measurement during the first wave of COVID-19 outbreak. We analyzed the positivity of FM levels (FM >7 g/mL) to assess the ability of FM monitoring during the first days of hospitalization to predict COVID-19 outcomes. Results: In our cohort, 935 FM measurements were performed in 246 patients during their first nine days of hospitalization. During patient follow-up, FM levels were higher in patients admitted directly to ICU than those admitted to MW. Moreover, we observed significantly increased levels of FM in patients when the data were stratified in-hospital mortality. At hospital admission, only 27 (11%) patients displayed a positive value for FM; this subgroup did not differ from other patients in term of severity (indicated by ICU referral at admission) or in-hospital mortality. When analyzing FM positivity in the first 9 days of hospitalization, we found that 37% of the patients had positive FM at least once during hospitalization and these patients had increased in-hospital mortality (p=0.001). Thus, we performed non-adjusted Kaplan–Meier curves for in-hospital mortality according to FM positivity during hospitalization and we observed a statistically significant difference for in-hospital mortality (HR=1.48, 95% CI 1.25−1.76, p<0.001). However, we compared the AUC of FM positivity associated with ratio of D-dimer >70% and found that this combined ROC curve was superior to the FM positivity ROC curve alone. Conclusion: Monitoring of FM positivity in hospitalized patients with COVID-19 could be a reliable and helpful tool to predict COVID-19 worsening and mortality.